A Challenge to Local Primitivism in Eastern European Cultures: the African ‘Exotic Heritage’ in Modern Art - Văetişi Șerban (Meno Istorija ir Kritika)
This article deals with the ‘primitivist’ sources of European modern art, with a focus on Eastern European artists, including some who later developed their careers in the West. These artists are regarded as atypical but relevant cases of modernist legacies, yet their contribution is less studied because of their non-Western European backgrounds. Their early artistic careers were influenced by the local folk and naïve style and motifs of their rural homelands, but they later transmuted their ‘primitivist style’, adopting the fashionable exotic, mostly African, motifs of the Western modernist schools when they moved to the West (typically, France), connected themselves with the modernist movement and received recognition. Unlike the perspective usually adopted by art criticism, this article suggests a heritage studies approach: it firstly conceptualises and considers how one type of heritage primitivism is subsumed to another in this complex artistic formation, and then problematises this dissonant legacy of their work. It is argued that in the field of cultural heritage debate, we need to extend the concept of dissonant heritage to discuss the dual concept of local/exotic heritage, while critically reassessing the uses of primitivism in its authenticist vs. assimilationist ideological intentions.